Collagen glycosylation, hip structural analysis, and trabecular bone score in adolescents with type 1 diabetes: a cross-sectional study - Sowmya Krishnan; Christopher E. Aston; Jennifer Chadwick; Shelly Gulati; Huaiwen Wang; Susan B. Sisson; Madhusmita Misra; Steven D. Chernausek (Diabetology & Metabolic Syndrome)
Abstract Both type 1 and type 2 diabetes mellitus (T1D and T2D) are associated with poor bone health and an increased risk of fracture in adults. However, there are limited data regarding the effects of diabetes on the growing skeleton, particularly during adolescence, the time of peak bone mineral accretion. The purpose of this study was to examine differences in markers of bone health and factors that influence bone health in White adolescents and young adults with well-controlled T1D (n = 17; Average A1C 7.45 ± 1.15%) and control participants without T1D (n = 13). Age across both groups was similar (17.41 ± 1.62 years for T1D vs. 17.46 ± 1.45 years for controls) as was BMI and height. Bone density was measured at the lumbar spine, whole body, and proximal femur sites using the GE HealthCare’s Lunar iDXA (GE; v11-30.062) in all subjects. Hip structural analysis (HSA) was performed at the proximal femur and Trabecular Bone Score (TBS) was calculated from AP spine image using Trabecular Osteo Software from Medimaps. Markers of bone formation, resorption, serum sclerostin and urine pentosidine were measured in all subjects. No difference in total body bone mineral density (BMD), lumbar spine BMD, lumbar spine BMAD, dual femur BMD, HSA variables or TBS measures were noted between subjects with T1D and controls. However, duration of diabetes had a significant negative correlation (p: 0.035) with cross-sectional moment of inertia (a measure of resistance to bending forces) in subjects with T1D. IGF-1 levels were marginally lower in the group with T1D (p:0.06) and had a significant inverse relationship (r: -0.406, p:0.026) with mean hip axis angle; a known predictor of hip fractures. TBS score had a marginally significant negative correlation with urinary pentosidine (a marker for collagen glycosylation) across both groups after adjusting for age (r: -0.343, p: 0.07), suggesting increased collagen glycosylation has an adverse impact on bone microarchitecture. Clinical trial number Not applicable